Analisis perencanaan pendidikan karakter peserta didik di kelas V sekolah dasar pada masa pandemi covid-19 - Bella Debora Septania; Sri Marmoah; Hadiyah Hadiyah (Didaktika Dwija Indria, 2023)
This research describes character education plans for fifth grade students at SD Angkasa Lanud Adi Soemarmo Colomadu during the co-19 pandemic. This research is a qualitative descriptive research with a case study approach. The research subjects were school principals, deputy principals, class V teachers, fifth grade students, and guardians of fifth grade students at SD Angkasa Lanud Adi Soemarmo Colomadu. Collecting data in this study through observation, interviews, and documentation studies. The data validity technique uses technique triangulation and source triangulation. The data was then analyzed qualitatively consisting of three components, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that character education planning includes character education planning meetings, identification of school activities, socialization of character education programs, provision of supporting facilities for character education.